Resposta :
Resposta:
[tex]\sf y=(2x-x^2)\cdot(x^3+4x^2)[/tex]
Pra derivar essa função aplique a regra do produto, na qual:
- [tex]\sf (f\cdot g)'=f'\cdot g+f\cdot g'[/tex]
Lembrando dessas outras regras de derivação:
- [tex]\sf (f\pm g)'=f'\pm g'[/tex]
- [tex]\sf(ax^n)'=anx^{n-1}, n > 1[/tex]
- [tex]\sf(ax^1)'=a[/tex]
Isto é:
[tex]\sf y'=[(2x-x^2)\cdot(x^3+4x^2)]'[/tex]
[tex]\sf y'=(2x-x^2)'\cdot(x^3+4x^2)+(2x-x^2)\cdot(x^3+4x^2)'[/tex]
[tex]\sf y'=[(2x)'-(x^2)']\cdot(x^3+4x^2)+(2x-x^2)\cdot[(x^3)'+(4x^2)'][/tex]
[tex]\red{\boxed{\sf y'=(2-2x)\cdot(x^3+4x^2)+(2x-x^2)\cdot(3x^2+8x)}}[/tex]
Letra D